2012
DOI: 10.1016/j.lfs.2012.07.006
|View full text |Cite
|
Sign up to set email alerts
|

The novel ETA receptor antagonist HJP-272 prevents cerebral microvascular hemorrhage in cerebral malaria and synergistically improves survival in combination with an artemisinin derivative

Abstract: Aim To investigate the association between vasculopathy and survival during experimental cerebral malaria (ECM), and to determine whether targeting the endothelin-1 (ET-1) pathway alone or in combination with the anti-malaria drug artemether (a semi-synthetic derivative of artemisinin) will improve microvascular hemorrhage and survival. Main Methods C57BL/6 mice infected with Plasmodium berghei ANKA (PbA) were randomly assigned to four groups: no treatment, artemether treated, ETA receptor antagonist (HJP-27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 37 publications
2
37
0
Order By: Relevance
“…12,13,15,16 B6 mice infected with P. berghei NK65 (PbN) do not develop neurological signs, die after 12 days postinfection, and are widely accepted as a control infection model for the B6-PbA model. Endothelin-1 (ET-1) is thought to contribute to the pathogenesis of human CM.…”
Section: Cerebral Malaria (Cm) Is the Deadliest Complication Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13,15,16 B6 mice infected with P. berghei NK65 (PbN) do not develop neurological signs, die after 12 days postinfection, and are widely accepted as a control infection model for the B6-PbA model. Endothelin-1 (ET-1) is thought to contribute to the pathogenesis of human CM.…”
Section: Cerebral Malaria (Cm) Is the Deadliest Complication Ofmentioning
confidence: 99%
“…Endothelin-1 (ET-1) is thought to contribute to the pathogenesis of human CM. 20,21 Our group recently demonstrated that ET-1 is involved in ECM vasculopathy 13,14 ; however, there are still significant gaps in understanding how ET-1 modulates brain vascular physiology during malaria infection. ET-1 is a potent regulator of the vascular tone, with mitogenic, apoptotic, and immunomodulatory properties.…”
Section: Cerebral Malaria (Cm) Is the Deadliest Complication Ofmentioning
confidence: 99%
“…Moreover, the P. berghei Anka infection model also allows investigations into liver damage, as described in Plasmodium-infected humans (8,9). Observations from humans with CM due to P. falciparum, as well as those from the CM mouse model using P. berghei Anka, suggest that the pathogenesis of CM is multifactorial and includes sequestration of infected red blood cells (iRBCs), disruption of the blood-brain barrier (BBB), upregulation of the inflammatory pathways, and dysregulation of endothelin pathways (10)(11)(12)(13). Previously, we have demonstrated a crucial role for platelet-activating factor in experimental CM infection (10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Observations from humans with CM due to P. falciparum, as well as those from the CM mouse model using P. berghei Anka, suggest that the pathogenesis of CM is multifactorial and includes sequestration of infected red blood cells (iRBCs), disruption of the blood-brain barrier (BBB), upregulation of the inflammatory pathways, and dysregulation of endothelin pathways (10)(11)(12)(13). Previously, we have demonstrated a crucial role for platelet-activating factor in experimental CM infection (10)(11)(12)(13). Infection with P. berghei Anka results in a reduction in cerebral blood flow and neuronal dysfunction (14,15).…”
mentioning
confidence: 99%
“…In the last 5 years, several novel compounds have been tested in animal models or in humans as adjunct therapy to prevent tissue and brain alterations during infection, including erythropoietin (EPO) (2,12), defibrotide (13), atorvastatin (14,15), the exogenous nitric oxide (NO) donor dipropylenetriamine-NONOate (16), and others (17,18). EPO, atorvastatin, and NO have undergone U.S. FDA review and been approved for other indications.…”
mentioning
confidence: 99%